The Barrier skink Oligosoma judgei n. sp. (Reptilia: Scincidae) from the Darran and Takitimu Mountains, South Island, New Zealand - Patterson, Geoff B; Bell, Trent P (Zootaxa, 2009)
A new species of alpine skink, Oligosoma judgei, is described from the Darran and Takitimu Mountains, South Island, New Zealand. This species is diagnosed on the basis of morphological, ecological, and genetic differentiation from the following congeners: O. pikitanga, O. acrinasum, O. infrapunctatum, O. otagense, O. taumakae, O. waimatense and O. grande. The new species is characterized by a black base colour with bright green or yellow dorsal speckles, a white belly with occasional black speckles, and distinctive head scalation. The conservation status of the new taxon appears secure due to the altitude and extensive habitat in the Darran Mountains and apparently wide range extending to the Takitimu Mountains.